-52=2(-3+4x)+2(3x-2)

Simple and best practice solution for -52=2(-3+4x)+2(3x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -52=2(-3+4x)+2(3x-2) equation:



-52=2(-3+4x)+2(3x-2)
We move all terms to the left:
-52-(2(-3+4x)+2(3x-2))=0
We add all the numbers together, and all the variables
-(2(4x-3)+2(3x-2))-52=0
We calculate terms in parentheses: -(2(4x-3)+2(3x-2)), so:
2(4x-3)+2(3x-2)
We multiply parentheses
8x+6x-6-4
We add all the numbers together, and all the variables
14x-10
Back to the equation:
-(14x-10)
We get rid of parentheses
-14x+10-52=0
We add all the numbers together, and all the variables
-14x-42=0
We move all terms containing x to the left, all other terms to the right
-14x=42
x=42/-14
x=-3

See similar equations:

| 12/t=6/3 | | (11x+10)+(8x+5)=(4x-5) | | 6.6d=6.4d-3.62 | | 2s+-9=3 | | k-10*9=-k | | 1/3x+131/3=15 | | 1x+12=14-2x | | X2+y2=34X+y=2 | | 3t=2t+13 | | 7f-5=8f+5 | | 36−w=10;w | | 6=x4.5 | | 40x+18x-3=368 | | 2x+49=5x+10 | | 104+t=t | | z+13=3z-13 | | 3x-19=6(x-3) | | 14a=2a-6 | | -5.6c-19.46=12.96+5.28-3c | | -3x=-4.5 | | 38-x=44 | | 36^x=6^x-8 | | 2(-5+m)=-20 | | I=5+i-2*1-2i+3i*i | | Z=5+i-2*1-2i+3i*i | | 36x=6x-8 | | 35=3g-5 | | 16+20m=5m-16+19m | | -x/2+10=12 | | 81-m=90 | | 73=13+4s | | 40+x=135 |

Equations solver categories